25: QUANTITATIVE EVALUATION OF WINTER ROOST SITES OF THE RIO GRANDE TURKEY IN NORTH‐CENTRAL OKLAHOMA - Ben C. Crockett (Wildlife Society Bulletin)
ABSTRACT This study was conducted to find and measure characteristics of winter roost sites of the Rio Grande turkey (Meleagris gallopavo intermedia Sennett), which has been successful in establishing itself in its new habitat. Roost sites were compared with control plots to determine differences in roost and nonroost areas. All roost sites measured were similar with respect to basal area, tree height, and tree density. Trees in roost areas tended to be taller and larger in diameter at breast height (dbh) than trees in nonroost areas. Mature American elms (Ulmus americana) were the most frequently used roost trees. Other species of large trees, such as sycamore (Platanus occidentalis), eastern cottonwood (Populus deltoides), bur oak (Quercus macrocarpa), and sugar hackberry (Celtis laevigata), were used to a lesser extent. Land surrounding roost sites was predominately open pasture, with smaller amounts in upland timber, cropland, and bottomland forests.